Higher Order Thinking Skills (HOTS) Siswa SD Melalui Model Pembelajaran RADEC (Read, Answer, Discuss, Explain, Create) Pada Membaca Di Pelajaran IPS - Rifa Kurnia Agriyana (SEHRAN (Jurnal Pendidikan Sejarah dan Kewarganegaraan), 2023)
This research was conducted to study primary student Higher Order Thinking Skills through the RADEC learning model. This study uses a quasi-experimental method with a suitable pretest-posttest control group design. Research subjects were 31 students who took part in RADEC learning and 28 students who took conventional learning (ongoing learning). All of these students are elementary school students in Cimanggung District, Sumedang Regency. The research instrument used was an observation sheet, a test item that had been discussed by experts, and a reading habits questionnaire. Data processing was carried out using SPSS version 24. The results showed that the implementation of RADEC was able to improve HOTS of primary school students on the topic of recycling, RADEC learning was able to improve reading skills of Primary students, as well as significantly providing benefits for HOTS students of RADEC learning and Conventional learning.